2020
DOI: 10.1186/s12955-020-01586-8
|View full text |Cite
|
Sign up to set email alerts
|

Persian version of the brief Older People’s Quality of Life questionnaire (OPQOL-brief): the evaluation of the psychometric properties

Abstract: Background and objective Quality of life (QoL) is a multi-dimensional concept and its assessment is one of important themes of care for older people. Assessing QoL in older people needs specific scales. The aim of this study was to culturally adapt and investigate the psychometric properties of the Persian version of brief Older People’s Quality of Life questionnaire (OPQOL-brief) in an Iranian older population. Methods This methodological cross-sectional study was conducted among 525 Persian-speaking older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…The ICC coefficient values (ICC = 0.904) were also satisfactory. Satisfactory reliability and internal consistency of the OPQoL-brief scale was found by Bowling et al [ 6 ], but also Feizi and Heidari [ 40 ] in the Persian version and Caliskan et al [ 35 ] in the Turkish version. Haugan et al [ 33 ] found better reliability of the scale when excluding 5 items for a sample of seniors in nursing homes.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The ICC coefficient values (ICC = 0.904) were also satisfactory. Satisfactory reliability and internal consistency of the OPQoL-brief scale was found by Bowling et al [ 6 ], but also Feizi and Heidari [ 40 ] in the Persian version and Caliskan et al [ 35 ] in the Turkish version. Haugan et al [ 33 ] found better reliability of the scale when excluding 5 items for a sample of seniors in nursing homes.…”
Section: Discussionmentioning
confidence: 85%
“…The two-factor model showed acceptable but lower reliability and validity. Feizi and Heidari [ 40 ] present a three-factor model, namely socioeconomic well-being (5 items), emotional well-being (5 items), and physical well-being (4 items).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Del mismo modo, en el año 2008 Ann Bowling e investigadores de la universidad de Gran Bretaña desarrollaron el cuestionario denominado: "Calidad de Vida de las Personas Mayores" (OPQOL-35) en su idioma original, en el cual se empleó una muestra de 987 adultos mayores ingleses de más de 65 años, para sustentar su hipótesis que describe a la calidad de vida como un constructo multifactorial (Bowling & Rai, 2009;Mares, Cigler & Vachkova, 2016), posteriormente se publica su versión corta OPQOL-Bref en el 2013 que consta de 13 ítems considerados los más importantes por los encuestados, descartando 22 ítems del cuestionario original, demostrando ser una herramienta útil cuando se requiere una evaluación corta e implacable (Bowling et al, 2013), de igual manera se han realizado investigaciones para validar las versiones traducidas del cuestionario; es el caso de una muestra de 478 participantes, quienes reflejaron niveles altos de satisfacción en su calidad de vida, en siete dominios principales, quienes mantienen autonomía en sus actividades diarias y viven solo o con pareja, a diferencia de aquellos que se encuentran bajo el cuidado de residencias, tutores, familiares; la validez y confiablidad en esta investigación osciló entre 0.72 y 0.90 para su versión en checo (Mares, Cigler & Vachkova, 2016), referente a su versión reducida que consta de 7 dimensiones, se realizó la validación en 168 participantes para su versión en turco, donde se encontró que el cuestionario es rentable y cuenta con una buena consistencia interna para el resultado de sus subescalas (Caliskan et al, 2019), 521 personas adultas mayores que viven solas participaron en un estudio que utilizó la versión adaptada al idioma chino, presentando resultados confiables en las 8 dimensiones y ubicándolo como instrumento idóneo para evaluar la calidad de vida en adultos mayores que viven solos (Chen & While, 2019), en otro contexto sociocultural participaron 764 adultos mayores quienes respondieron el cuestionario en su versión e idioma original, reflejando que la calidad de vida está estrechamente relacionado a una buena salud física y emocional, independencia, toma de decisiones y control sobre su vida (Siriwardhana et al, 2019), en su versión persa los resultados de 500 y 525 participantes demostraron su utilidad para evaluar la calidad de vida en edades avanzadas para población de habla persa (Nikkhah et al, 2018;Feizi & Heidari, 2020).…”
Section: Introductionunclassified
“…It was also used in several studies in Albania (27), India (28), Sri Lanka (29), Pakistan (30), Malesia (31) and Indonesia (32). Some countries, such as Turkey (33), Iran (34) and Norway (35), translated and used the OPQOL-brief with thirteen items. Although French is spoken by about 300 millions of people in the world, making it the fifth most widely used language in the world (36), the OPQOL- 35 is not yet available in French.…”
Section: Introductionmentioning
confidence: 99%